TRPS1 inhibits cervical cancer progression by suppressing ORC6-mediated tumor stemness - Juan He; Ruyu Yan; Yitong Du; Huiling Yang; Yichen Feng; Min Tian; Zejun Wu; Lei Li; Lan Xiang; Duoxiang Sun; Xianghua Li; Kecheng Zhou; et al. (Tissue and Cell, 2026)

Differential adsorption and diffusion mechanism of CO2 in clay slit pores: Implications for structural control on geological sequestration - Yichen Wang; Yang Wang; Hongfei Cheng; Ziwei Ding; Ni He (Applied Clay Science, 2026)

Intercropping enhances soil aggregate stability and associated organic carbon via divergent microbial assembly and co-occurrence networks - Yazhen Chen; Wenqiong Jiang; Yuanying Peng; Yichen Xu; Haobo Xu; Juan Chen; Xiaozhou Huang; Jinsong He; Xiaohong Wu; Jun Wang; Jianbo Jia; Wende Yan (Agriculture, Ecosystems & Environment, 2026)

Does Forest Rights Mortgage Credit Involve Elite Capture? An Empirical Analysis in Collective Forest Areas of Liaoning, China - Yuanyuan Guo; Yichen Jiang; Ke Chen; Dan He (Small-scale Forestry, 2026)

Coupled acid–salt erosion mechanism of solid waste–based grouting materials for submarine tunnels - Jun Ma; Weiyu Liu; Annan Jiang; Yichen Deng; Jiale Zhao; Tianmiao Qu; Chao He (Marine Georesources & Geotechnology, 2026)

A rapid optimization framework for high-rise office block design elements driven by carbon emission performance: Perspectives from three climate zones in China - Shen Xu; Qiuguo He; Tao Luo; Yichen Dong; Hua Zhong; Junchao Duan; Gaomei Li (Sustainable Cities and Society, 2026)

Preparation of valuable furil catalyzed by flower-like ternary metal oxides under mild conditions - Zhenwei Yuan; Kun Yuan; Yichen Zou; Jian Kang; Dan Hou; Jianping Huang; Jing Chen; Lu He; Hualin Jiang; Wanming Xiong (Journal of Environmental Chemical Engineering, 2026)

Assessment and simulation of carbon storage in high-groundwater coal basins based on detailed water body classification: a case study of the Yanzhou Coalfield, China - Yanan He; Yanhua Fu; Li Wang; Wenqi Chen; Wu Xiao; Yichen Shi; Zhengshan Ju (Environmental Monitoring and Assessment, 2026)

Shift in orbital-scale climate response under the coupling of ice sheet and monsoon during the Late Oligocene: Sedimentary records from the East China Sea Shelf Basin - Yingkun Cui; Fujie Jiang; Xianke He; Yichen Liu; Wenji Wang; Rui Zhang; Yinghui Liu; Zhuo Li; Zhenguo Qi; Bo Xu; Hang lv; Jiming Shi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Engineering a tetrahedral framework nucleic acid-based nanomedicine for precise intracellular delivery of rapamycin to rescue senescent bone mesenchymal stem cells - Shibo Liu; Qiheng Yang; Hanghang Liu; Ze He; Xuehan Tang; Yichen Yang; Yunfeng Lin; En Luo (Chemical Engineering Journal, 2026)

Vehicle-induced bridge dynamic response monitoring and displacement estimation using distributed acoustic sensing - Yichen Zhong; Chen Gu; Peng Wu; Zhanxiong Ma; Zhi Yuan; Zhuoyu Chen; Jiawei He; Chenrui Fan; Jiahui Wang; Dikai Wang; Xinzheng Lu (Engineering Structures, 2026)

Dual-source-driven snowman-shaped PMO@MnO2@C@DMSN-SS31 Janus nanomotors for enhanced deep penetration and restoration of mitochondrial function to modulate the inflammatory microenvironment for cartilage repair - Xiaolei Zhang; Zhihan An; Yichen Zhang; Jinquan Cui; Qiang He; Chuandong Cai; Jianing Liu; Zhentao Man; Wei Li (Chemical Engineering Journal, 2026)

Skin-triggered Janus physical cooling patches for prolonged evaporative cooling and superior comfort - Junyi Lu; Fuzhou Niu; Tonghuan Zhan; Heng Wang; Haojun Luo; Yichen Tang; He Wang; Xiaohua Yu; Weijie Zhang; Hao Chen; Bing Xu (Chemical Engineering Journal, 2026)

Targeted breeding of Litopenaeus vannamei for resistance to acute hepatopancreatic necrosis disease using the IRF-SSR molecular marker - Bin Yin; Yang Hu; Xuheng Yan; Yibin Chen; Yichen Hu; Sedong Li; Chaozheng Li; Jianguo He (Aquaculture, 2026)

Origin and diagenetic evolution of claystones in the CP2 coal seam, Adaohai Mine, Daqingshan Coalfield: Evidence from mineralogy and geochemistry - Ni He; Shangying Li; Hongfei Cheng; Zhenxiao Wu; Yichen Wang; Shaoxian Liang (International Journal of Coal Geology, 2026)

Dynamically programmable plant-derived scaffold coordinates alveolar bone repair cascade: Phase-adaptive integration from hemostasis to bone remodeling - Yeke Chen; Yumei Ning; Fang Dai; Yuting Yang; Chenjiang He; Kaiqiang Yang; Yichen Hu; Guoping Cheng; Li Song (Chemical Engineering Journal, 2025)

Cellular optical imaging techniques: a dynamic advancing frontier - Yaning Li; Chuankang Li; Caiwei Zhou; Jie Wang; Weixing Li; Tianying Pan; Chenying He; Xiaodong Guan; Yichen Wang; Yingda Huang; Xianao Zhao; Lusheng Gu; et al. (Science China Life Sciences, 2025)

Enhanced conductivity and energy storing performances of 3D bimetallic conductive metal-organic frameworks based on linear π-conjugated thiazole for supercapacitors - Chungui Wang; Yichen He; Junping Xie; Siyi Wang; Yingjun Chen; Xu Yang; Yong Pei; Naien Shi; Mong-Feng Chiou; Linghai Xie; Xiaomiao Feng; Min Han (Chemical Engineering Journal, 2025)

Mechanisms of aristolochic acid I Hepatotoxicity: Central role of PDK4-Induced mitochondrial dysfunction and hepatic inflammation - Zhaobin Wang; Kunyang Li; Xiaoqi Yi; Yichen Wu; Yang Zhao; Pingping He; Qinghua Zeng; Enxiang Zhang (Food and Chemical Toxicology, 2025)

Tetrahedral framework nucleic acid-based delivery of microRNA-29b: A precision nanotherapeutic strategy for oral submucous fibrosis - Xiao Fu; Mei Zhang; Chenpeng Chen; Xin Qin; Qianqian He; Yichen Yang; Siqi Xu; Guanjun Chen; Haiyu Xian; Guanyu Sun; Yao He; Yunfeng Lin; et al. (Chemical Engineering Journal, 2025)

Human dental follicle cell-derived conditioned media enhance periodontal regeneration by regulating the osteogenic differentiation and inflammation of periodontal ligament stem cells and macrophage polarization - Yichen Gao; Xianyi He; Yuyao Deng; Xia Wang; Jie Shen; Wei Xu; Rui Cai; Xiaorong Lan; Junliang Chen; Yun He (Molecular and Cellular Biochemistry, 2025)

High water demand limits carbon sink and transpiration in tall forests during extreme drought in Southwest China - Peipei Xu; Yichen Cao; Wei Fang; Wei He; Zuo Wang; Hua Yang; Lisheng Song (Agricultural and Forest Meteorology, 2025)

Bacterial cellulose and photothermal material from biomass-based zero-waste biorefinery functionalized chitosan film for sustainable active food packaging - Li Yang; Wenyang Sheng; Yichen Yang; Ying Yang; Kaiwen He; Guangyang Jiang; Yongqiang Tian (Food Hydrocolloids, 2025)

Treatment of rheumatoid arthritis via tetrahedral framework nucleic acid‑based efficient delivery of Jakinib: Synergistic anti-inflammatory and osteogenic effects - Yichen Yang; Ruiqing Wang; Wumeng Yin; Ziqi Yue; Yuxuan Zhao; Zhou Jiang; Yunfeng Lin; Yao He; Shaojingya Gao; Xiaoxiao Cai (Chemical Engineering Journal, 2025)

Impact of fallen wood on soil protists in the subtropics - Yichen Xu; Yini Cao; Yazhen Chen; Zhe He; Wende Yan; Jun Wang (Plant and Soil, 2025)

Metagenomics reveals an increased proportion of an Escherichia coli-dominated enterotype in elderly Chinese people - Jinyou Li; Yue Wu; Yichen Yang; Lufang Chen; Caihong He; Shixian Zhou; Shunmei Huang; Xia Zhang; Yuming Wang; Qifeng Gui; Haifeng Lu; Qin Zhang; et al. (Journal of Zhejiang University-SCIENCE B, 2025)

Janus antistatic protective clothing for personal sweat management and electrostatic protection - Haojun Luo; Yichen Tang; Xianchang Wu; Yu Zhang; Shuqiang Min; Yijie Zhu; He Wang; Tonghuan Zhan; Zixuan Xu; Zhihao Chen; Xiaohua Yu; Heng Wang; et al. (Chemical Engineering Journal, 2025)

Exploring tourists' perceptions of ecosystem services in national parks to guide the optimization of management - Xiaomin Xiao; Yichen Yan; Yuxin Qi; Qiaoru Ye; Qiwen Yu; Keren He; Ruiming Xiao; Xue-Chao Wang; Xiaobin Dong (Journal of Cleaner Production, 2025)

Greener is not always better: Exploring the non-linear relationships between three-dimensional green and gray spaces exposure and various physical activities - Yuheng Mao; Tianyu Xia; Fan Hu; Jinyu Hu; Yichen He; Jingheng Yan; Ling Wang; Hongmei Xu; Jinguang Zhang; Dan Chen (Building and Environment, 2025)

Zero-carbon renewal of communities through collaborative retrofitting of multi-scale design elements: A case of Wuhan, China - Shen Xu; Huangwanjin Zhou; Yichen Dong; Qiuguo He; Gaomei Li (Energy and Buildings, 2025)

Development of multifunctional chitosan packaging film by plasticizing novel essential oil-based hydrophobic deep eutectic solvent: Structure, properties, and application - Guangyang Jiang; Kaiwen He; Mingrui Chen; Yichen Yang; Tingting Tang; Yongqiang Tian (Carbohydrate Polymers, 2025)

PupaNet: A versatile and efficient silkworm pupae (Bombyx mori) identification tool for sericulture breeding based on near-infrared spectroscopy and deep transfer learning - Haibo He; Hua Huang; Shiping Zhu; Lunfu Shen; Zhimei Lv; Yongkang Luo; Yichen Wang; Yuhang Lin; Liang Gao; Benhua Xiong; Fangyin Dai; Tianfu Zhao (Computers and Electronics in Agriculture, 2024)

Midseason drying increases soil dissolved organic carbon and rice yield via soil cbbL bacteria - Jinsong He; Wei Wang; Ting Liu; Wende Yan; Xiaohong Wu; Junjie Lei; Yichen Xu; Yazhen Chen; Yuxin Yao; Wenqiong Jiang; Zhentao Shen; Asma Farooq (Journal of Environmental Management, 2024)

Nitrogen availability and its related enzyme activities affect microbial residue nitrogen accumulation during Chinese fir plantation development - Junjie Lei; Peng Dang; Xiaoqian Gao; Yichen Xu; Ting He; Zongxin Liu; Wende Yan (Applied Soil Ecology, 2024)

Lightweight, high-strength and fireproof borax-crosslinked graphene/hydroxyethyl cellulose hybrid aerogels fabricated via ice template method - Junjiao Li; Chao Sui; Chenxi Zhao; Gong Cheng; Zifu Zang; Lei Wen; Yuna Sang; Yichen Zhou; Yushun Zhao; Xin Yan; Xiaodong He; Chao Wang (Chemical Engineering Journal, 2024)

Suppression of pathological neovascularization by anti-Flt1 peptide functionalized DNA tetrahedron - Bicai Tang; Yuting Yang; Yong Li; Yutian He; Yichen Ge; Yangxue Yao; Wenjuan Ma; Yunfeng Lin (Chemical Engineering Journal, 2024)

Robust and tunable hydrogels strengthened by dynamic amphiphilic ionic domains - Wenzhe Xiao; Ting He; Wanting Zhao; Wenjin Li; Yichen Liu; Cheng Li; Qizhen Luo; Weidong Zhao; Jipeng Yan; Jian Sun (Chemical Engineering Journal, 2024)

Numerical simulation of the cloud seeding operation of a convective rainfall event occurred in Beijing - Shaofeng Hua; Baojun Chen; Hui He; Yichen Chen; Xiang’e Liu; Jing Yang (Atmospheric Research, 2024)

Environmental temperature variations drive the changes of microbial communities to affect Baijiu flavor quality: Case study of Qingxiangxing Baijiu - Qiao Huang; Ying Liu; Zongjun He; Yichen Mao; Hui Wu; Lei Tian; Shuangquan Xiang; Liuzhu Long; Yang Li; Tongwei Guan (Food Bioscience, 2024)

The greener the living environment, the better the health? Examining the effects of multiple green exposure metrics on physical activity and health among young students - Yuheng Mao; Tianyu Xia; Fan Hu; Dan Chen; Yichen He; Xing Bi; Yangcen Zhang; Lu Cao; Jingheng Yan; Jinyu Hu; Yanzi Ren; Hongmei Xu; et al. (Environmental Research, 2024)

Dynamics of carbon storage driven by land use/land cover transformation in coal mining areas with a high groundwater table: A case study of Yanzhou Coal Mine, China - Yanhua Fu; Yanan He; Wenqi Chen; Wu Xiao; He Ren; Yichen Shi; Zhenqi Hu (Environmental Research, 2024)

Short-term high temperature may increase the incidence risk of collective conflicts: A case-crossover study in the Greater Middle East - Yichen Guo; Ya Gao; Cheng He; Yixiang Zhu; Lu Zhou; Haidong Kan; Renjie Chen (Science of The Total Environment, 2024)

Development of a dual-functional inhibitor for natural gas hydrates and construction of drilling fluid system - Jintang Wang; Zhijun He; Yichen Yan; Lei Liu; Jin Yan; Bo Liao; Ke Zhao; Yiyao Li; Longqiao Chen (Gas Science and Engineering, 2024)

Microphysical and dynamic evolution of convection observed by polarimetric radar under the influence of cloud seeding - Hepeng Zheng; Yun Zhang; Yichen Chen; Deping Ding; Zuhang Wu; Mengyu Huang; Hui He; Xincheng Ma; Zeming Zhou (Atmospheric Research, 2024)

Long-term spatiotemporal variations in surface NO2 for Beijing reconstructed from surface data and satellite retrievals - Zixiang Zhao; Yichen Lu; Yu Zhan; Yuan Cheng; Fumo Yang; Jeffrey R. Brook; Kebin He (Science of The Total Environment, 2023)

Promoting microbial community succession and improving the content of esters and aromatic compounds in strong-flavor Daqu via bioaugmentation inoculation - Pei Xu; Yijiao Wu; Hang Chen; Ying Liu; Na Yang; Yichen Mao; Lei Tian; Zongjun He; Xianping Qiu; Tongwei Guan (Food Bioscience, 2023)

Electroacupuncture Inhibits Pain Memory and Related Anxiety-Like Behaviors by Blockading the GABAB Receptor Function in the Midcingulate Cortex - Xiaoyu Li; Yichen Zhu; Haiju Sun; Zui Shen; Jing Sun; Siqi Xiao; Xiaofen He; Boyu Liu; Yifang Wang; Yuxin Hu; Boyi Liu; Yi Liang; et al. (Molecular Neurobiology, 2023)
Pain memory is commonly considered an underlying cause of chronic pain and is also responsible for a range of anxiety. Electroacupuncture (EA) has been shown to ameliorate pain memories and exert anti-anxiety effects. Previous research has indicated that GABAergic neurons and/or GABA receptors (GABARs) in the midcingulate cortex (MCC) have potential associations with chronic pain and anxiety. However, there is no known empirical research that has specifically studied the effects of EA on the GABAergic system in the MCC. Here, we used cross-injection of carrageenan to establish the pain memory rats model. Immunofluorescence were used to detect the excitability of GABAergic neurons within MCC. Von Frey filament, elevated zero maze, and open field tests were used to measure mechanical allodynia and anxiety-like behaviors, combined with chemogenetic and pharmacologic technologies. Finally, this study provides evidence that pain memories contribute to generalized negative emotions and that downregulating the activity of GABAergic neurons within MCC could block pain memories and reverse anxiety emotion. Specifically, GABA B R is involved in pain memory and related anxiety-like behaviors. Activation of GABAergic neurons in the MCC did not reverse the effects of EA on pain memories and related anxiety-like behaviors, whereas these effects could be reversed by a GABA B R agonist. These findings highlight the functional significance of GABA B R in the EA-mediated attenuation of pain memories and related anxiety-like behaviors in rats.

Camouflaging multifunctional nanoparticles with bacterial outer membrane for augmented chemodynamic/photothermal/starvation/chemo multimodal synergistic therapy of orthotopic glioblastoma - Yichen He; Yi Pan; Xin Zhao; Luyi Ye; Longcai Liu; Wenliang Wang; Meng Li; Dapeng Chen; Yu Cai; Xiaozhou Mou (Chemical Engineering Journal, 2023)

Dual photoelectrodes activate oxygen evolution and oxygen reduction reactions enabling a high-performance Zn-air battery and an efficient solar energy storage - Jia You; Bingqing Zhang; Xianlong Wang; Haoran Zhang; Lanlan Huang; Lihua He; Nanxin Li; Yichen Chang; Shiwei Lin (Chemical Engineering Journal, 2023)

AGHRNet: An attention ghost-HRNet for confirmation of catch‐and‐shake locations in jujube fruits vibration harvesting - Zhouzhou Zheng; Yaohua Hu; Taifeng Guo; Yichen Qiao; Yong He; Yan Zhang; Yuxiang Huang (Computers and Electronics in Agriculture, 2023)

Production of 1,3-propanediol using enzymatic hydrolysate derived from pretreated distillers' grains - Li Yang; Guangyang Jiang; Jia Chen; Zhe Xu; Yichen Yang; Bijun Zheng; Yi Yang; He Huang; Yongqiang Tian (Bioresource Technology, 2023)

Liquid water determination by airborne millimeter cloud radar and in-situ size distribution measurements - Dongfei Zuo; Dantong Liu; Delong Zhao; Ling Yang; Yichen Chen; Wei Zhou; Mengyu Huang; Hui He; Ping Tian; Yuanmou Du; Wei Xiao; Ruijie Li; et al. (Atmospheric Research, 2023)

Nanoplastics induce molecular toxicity in earthworm: Integrated multi-omics, morphological, and intestinal microorganism analyses - Ronggui Tang; Dong Zhu; Yongming Luo; Defu He; Haibo Zhang; Ali El-Naggar; Kumuduni Niroshika Palansooriya; Keyi Chen; Yan Yan; Xinghang Lu; Minshen Ying; Tao Sun; et al. (Journal of Hazardous Materials, 2023)

Electroacupuncture Alleviates Anxiety-Like Behaviors Induced by Chronic Neuropathic Pain via Regulating Different Dopamine Receptors of the Basolateral Amygdala - Mengwei Wu; Yeqing Chen; Zui Shen; Yichen Zhu; Siqi Xiao; Xixiao Zhu; Zemin Wu; Jinggen Liu; Chi Xu; Pingan Yao; Weiwei Xu; Yi Liang; et al. (Molecular Neurobiology, 2022)
Chronic pain, such as neuropathic pain, causes anxiety and other negative emotions, which aggravates the pain sensation and increases the risk of chronic pain over time. Dopamine receptor D1 (DRD1) and dopamine receptor D2 (DRD2) in the basolateral amygdala (BLA) have been implicated in mediating anxiety-related behaviors, but their potential roles in the BLA in neuropathic pain-induced anxiety have not been examined. Electroacupuncture (EA) is commonly used to treat chronic pain and emotional disorders, but it is still unclear whether EA plays a role in analgesia and anxiety relief through DRD1 and DRD2 in the BLA. Here, we used western blotting to examine the expression of DRD1 and DRD2 and pharmacological regulation combined with behavioral testing to detect anxiety-like behaviors. We observed that injection of the DRD1 antagonist SCH23390 or the DRD2 agonist quinpirole into the BLA contributed to anxiety-like behaviors in naive mice. EA also activated DRD1 or inhibited DRD2 in the BLA to alleviate anxiety-like behaviors. To further demonstrate the role of DRD1 and DRD2 in the BLA in spared nerve injury (SNI) model-induced anxiety-like behaviors, we injected the DRD1 agonist SKF38393 or the DRD2 antagonist sulpiride into the BLA. We found that both activation of DRD1 and inhibition of DRD2 could alleviate SNI-induced anxiety-like behaviors, and EA had a similar effect of alleviating anxiety. Additionally, neither DRD1 nor DRD2 in the BLA affected SNI-induced mechanical allodynia, but EA did. Overall, our work provides new insights into the mechanisms of neuropathic pain-induced anxiety and a possible explanation for the effect of EA treatment on anxiety caused by chronic pain.

Characteristics of an ore-controlling shear zone in the Cigou-Zaoyang gold mine area of Ankang, South Qinling Mountains, China - Hujun He; Yichen Zhao; Jian Zhang; Xingke Yang; Rui Xing; Wei Li (Arabian Journal of Geosciences, 2022)

Strong partitioning of soil bacterial community composition and co-occurrence networks along a small-scale elevational gradient on Zijin Mountain - Xu Liu; Teng Yang; Yu Shi; Yichen Zhu; Mulin He; Yunke Zhao; Jonathan M. Adams; Haiyan Chu (Soil Ecology Letters, 2021)

Efficiency comparison of B6(Cg)-Tyrc−2j /J and C57BL/6NTac embryos as hosts for the generation of knockout mice - Yu’e Ma; Lei He; Lijie Xiang; Jie Zhang; Jing Wang; Wenjing Zhu; Wenni Cao; Yichen Zhu; Man Gao; Fei Zhou; Zhiwei Liu (Transgenic Research, 2021)
Careful selection of the host embryo is critical to the efficient production of knockout (KO) mice when injecting mouse embryonic stem (mES) cells into blastocysts. B6(Cg)-Tyr c−2j /J (B6 albino) and C57BL/6NTac (B6NTac) strains of mice are widely used to produce host blastocysts for such procedures. Here, we tested these two strains to identify an appropriate match for modified agouti C57BL/6N (JM8A3.N1) mES cells. When comparing blastocyst yield, super-ovulated B6NTac mice produced more injectable blastocysts per female than B6 albino mice (8.2 vs. 5.4). There was no significant difference in birth rate when injected embryos were transferred to the same pseudopregnant recipient strain. However, the live birth rate was significantly higher for B6NTac blastocysts than B6 albino blastocysts (62.7% vs. 50.2%). In addition, the proportion of pups exhibiting high-level and complete chimerism, as identified by coat color, was also significantly higher in the B6NTac strain. There was no obvious difference in the efficiency of germline transmission (GLT) when compared between B6NTac and B6 albino host embryos (61.5% vs. 63.3% for mES clones; 64.5% vs. 67.9% for genes, respectively), thus suggesting that an equivalent GLT rate could be obtained with only a few blastocyst injections for B6NTac embryos. In conclusion, our data indicate that B6NTac blastocysts are a better choice for the microinjection of JM8A3.N1 mES cells than B6 albino blastocysts.

Investigation of Blade Tip Shape for Improving VAWT Performance - Yichen Jiang; Chenlu He; Peidong Zhao; Tiezhi Sun (Journal of Marine Science and Engineering, 2020)
Vertical axis wind turbine (VAWT) is a competitive power generation device due to structural simplicity, wind direction independence, no yaw mechanism required, easier maintenance, and lower noise emission. However, blade tip vortex will be generated at both ends of the blade during the rotation, resulting in torque loss and efficiency reduction. In this paper, computational fluid dynamics is used to study blade tip vortex and its reduction technique of a single-blade VAWT rotor in real scale. By monitoring the force and flow field at different heights of the blade, the influence ranges of tip vortex are obtained. The reduction effect of the bulkhead obtained from the blade profile curve is studied, and the size of the bulkhead is optimized. On the basis of adding the optimal bulkhead, the influence of the supporting strut is also explored. The joint action is obtained by changing the location of the supporting strut. The results show that the top supporting strut-bulkhead structure is the optimal position. The power-extraction efficiency of the rotor with this integrated structure is significantly improved at optimal tip speed ratios (TSRs) and higher TSRs.

Lower Cambrian polychaete from China sheds light on early annelid evolution - Jianni Liu; Qiang Ou; Jian Han; Jinshu Li; Yichen Wu; Guoxiang Jiao; Tongjiang He (The Science of Nature, 2015)

Systematic analysis of gene expression level with tissue-specificity, function and protein subcellular localization in human transcriptome - Qiang Li; Xianghua Liu; Quanyuan He; Lei Hu; Yichen Ling; Yanhua Wu; Xianmei Yang; Long Yu (Molecular Biology Reports, 2011)